Bacteriophage T4 rnh (RNase H) Null Mutations: Effects on Spontaneous Mutation and Epistatic Interaction with rII Mutations - Bebenek, Anna (American Society for Microbiology, 1999)
The bacteriophage T4 rnh gene encodes T4 RNase H, a relative of a family of flap endonucleases. T4 rnh null mutations reduce burst sizes, increase sensitivity to DNA damage, and increase the frequency of acriflavin resistance (Ac(r)) mutations. Because mutations in the related Saccharomyces cerevisiae RAD27 gene display a remarkable duplication mutator phenotype, we further explored the impact of rnh mutations upon the mutation process. We observed that most Ac(r) mutants in an rnh(+) strain contain ac mutations, whereas only roughly half of the Ac(r) mutants detected in an rnhΔ strain bear ac mutations. In contrast to the mutational specificity displayed by most mutators, the DNA alterations of ac mutations arising in rnhΔ and rnh(+) backgrounds are indistinguishable. Thus, the increase in Ac(r) mutants in an rnhΔ background is probably not due to a mutator effect. This conclusion is supported by the lack of increase in the frequency of rI mutations in an rnhΔ background. In a screen that detects mutations at both the rI locus and the much larger rII locus, the r frequency was severalfold lower in an rnhΔ background. This decrease was due to the phenotype of rnh rII double mutants, which display an r(+) plaque morphology but retain the characteristic inability of rII mutants to grow on λ lysogens. Finally, we summarize those aspects of T4 forward-mutation systems which are relevant to optimal choices for investigating quantitative and qualitative aspects of the mutation process.